Efficacy of the biocontrol agent Trichoderma hamatum against Lasiodiplodia theobromae on macadamia - Li, Xiaojiao; Leng, Jinsong; Yu, Longfeng; Bai, Haidong; Li, Xiaojun; Wisniewski, Michael; Liu, Jia; Sui, Yuan (Frontiers in Microbiology, 2022)
Macadamia (Macadamia integrifolia) trees are an important source of revenue in rainforest ecosystems. Their nuts are rich in vitamins, minerals, fiber, antioxidants, and monounsaturated oils. The fungus Lasiodiplodia theobromae, however, is a major disease problem, causing kernel rot and other disease symptoms. In the present study, a dual confrontation assay was used to evaluate the inhibitory effect of an endophytic strain of Trichoderma hamatum C9 from macadamia root against L. theobromae. Volatiles and cell-free culture filtrate of T. hamatum were also used to assess their antifungal activity against L. theobromae. Results suggested that T. hamatum exhibited a significant inhibitory effect against L. theobromae in vitro. Further results of a biocontrol assay indicated that a spray treatment of T. hamatum conidial suspension significantly decreased the size of lesions caused by artificially-inoculated L. theobromae on macadamia leaves, as well as the disease index in young trees inoculated with L. theobromae, relative to sterile water controls. Collectively, our findings indicate that T. hamatum C9 represents a potential biocontrol agent that can be used to manage L. theobromae on macadamia.